THE EFFECT OF EARLY WARNING SYSTEM IMPLEMENTATION ON EARLY DETECTION OF EMERGENCY CONDITIONS IN HOSPITALIZED PATIENTS: A DESCRIPTIVE CORRELATION STUDY - Intan , Intan Munawaroh; Ria, Ria Anggraini; Manggar, Manggar Purwacaraka; Lia, Lia Fadlilah; Intan Munawaroh (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Patient safety is a primary focus in healthcare services, particularly in the early detection of clinical deterioration among hospitalized patients. Delays in identifying signs of critical conditions may increase the risk of cardiac arrest, disability, and even death. The Early Warning System (EWS) is an instrument used to efficiently and accurately detect patient deterioration through structured monitoring of vital parameters. This study aimed to determine the relationship between the implementation of EWS and the early detection of emergency conditions in hospitalized patients. Method: This research employed a descriptive correlation design with a cross-sectional approach. The sample of 60 nurses with a total sample. Data were collected using observation instruments assessing EWS implementation and early detection capability. Data analysis was performed using the Chi-Square test. Results showed that most nurses demonstrated a moderate level of EWS implementation (61.6%), while the ability for early detection of emergency conditions was predominantly in the good category (71.6%). The Chi-Square test revealed a significant relationship between EWS implementation and early detection ability with a p-value of 0.001 (p < 0.05). This indicates that the more optimal the EWS implementation, the faster and more accurate nurses are in recognizing clinical deterioration. Conclusion: The importance of consistent EWS application as a preventive measure against critical events in patients. Hospitals are encouraged to strengthen training programs, supervision, and support facilities to optimize EWS performance and enhance patient safety outcomes.